Sex differences in performance and depth of field in the united states olympic trials - Jobe, T. K.; Shaffer, H. N.; Doci, C. L.; Gries, K. J. (The Journal of Strength and Conditioning Research, 2022)
Recently, there has been an increased discussion on the role of sex as a variable in human performance. Although there likely remains sociological factors, we can estimate biological sex differences in human performance by comparing finishing times in elite men and women. We sought to determine the effect of sex on running and swimming velocity and depth of field in events of varying lengths in the previous 25 years. Finishing times from United States Olympic trials in running events (100 m to marathon) and freestyle swimming (50-1,500 m) from 1996 to 2021 were collected. Sex differences in velocity were calculated for each year (trends), place (first through seventh), and depth of field (nth place/first place). Significance was set at p = 0.05. Men were 9-13% faster than women in all running events (p = 0.05). The 100-m dash (9%) had the lowest sex difference compared with races of longer distance (p = 0.05). In swimming, men were faster in all events (6-12%, p = 0.05), in which sex differences generally decreased with longer distances. Depth of field was similar between men and women in all running and swimming events. No differences in the analyzed variables were observed from 1996 to 2021. These data suggest that elite men are 9% faster in the 100 m compared with running races of longer distances (~12%). Sex differences in swimmers tended to get smaller as duration increased. Although participation and other sociological factors in these events may play a role, these sex differences warrant further discussion on the role of sex in athletic competition.